Birth Order and Myopia. (December 2013) - Guggenheim, Jeremy A.; McMahon, George; Northstone, Kate; Mandel, Yossi; Kaiserman, Igor; Stone, Richard A.; Lin, Xiaoyu; Saw, Seang Mei; Forward, Hannah; Mackey, David A.; Yazar, Seyhan; Young, Terri L.; et al.
Abstract Purpose: An association between birth order and reduced unaided vision (a surrogate for myopia) has been observed previously. We examined the association between birth order and myopia directly in four subject groups. Methods: Subject groups were participants in (1) the Avon Longitudinal Study of Parents and Children (ALSPAC; UK; age 15 years; N = 4401), (2) the Singapore Cohort Study of Risk Factors for Myopia (SCORM; Singapore; age 13 years; N = 1959), (3) the Raine Eye Health Study (REHS; Australia; age 20 years; N = 1344), and (4) Israeli Defense Force Pre-recruitment Candidates (IDFC; Israel; age 16–22 years; N = 888, 277). The main outcome was odds ratios (OR) for myopia in first-born versus non-first-born individuals after adjusting for potential risk factors. Results: The prevalence of myopia was numerically higher in first-born versus non-first-born individuals in all study groups, but the strength of evidence varied widely. Adjusted ORs (95% confidence intervals, CIs) were: ALSPAC, 1.31 (1.05–1.64); SCORM, 1.25 (0.89–1.77); REHS, 1.18 (0.90–1.55); and IDFC, 1.04 (1.03–1.06). In the large IDFC sample, the effect size was greater (a) for the first-born versus fourth- or higher-born comparison than for the first-born versus second/third-born comparison (p < 0.001) and (b) with increasing myopia severity (p < 0.001). Conclusions: Across all studies, the increased risk of myopia in first-born individuals was low (OR < 1.3). Indeed, only the studies with >4000 participants provided strong statistical support for the association. The available evidence suggested the relationship was independent of established risk factors such as time outdoors/reading, and thus may arise through a different causal mechanism.